Difference In VAS Value Before and After Physiotherapy In Osteoarthritis Patients At The Noble Heart General Hospital Kendari - Pingki; Muhammad Rustam; La Rangki (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2023)
Background: Osteoarthritis (OA) is a joint disease that most often occurs in adulthood to old age throughout the world, according to the world health organisation (WHO) in 2014 stated that the world's population experiencing osteoarthritis is 335 million people worldwide. Risk factors that affect the incidence of Osteoarthritis include age, gender, obesity, genetics, joint injury, exercise and work, and other risk factors. One of the OA treatments is physiotherapy to reduce the pain intensity of Osteoarthritis sufferers. This study aims to determine the difference in VAS values before and after physiotherapy in Osteoarthritis patients at the Mulia Hati General Hospital Kendari. Method: This study used a descriptive analytic method with a cross sectional approach. This research was conducted at the Mulia Hati General Hospital Kendari from November to December 2022. This sampling uses total sampling that meets the inclusion criteria with a total sample of 37 patients. Data analysis using the Wilcoxon test. Result: The results showed a P value of 0.000 (p value <0.05), so Ha was accepted, which means that the results of the research conducted showed a difference in VAS values before and after physiotherapy. Conclusio:. The conclusion of this study is a decrease in VAS value after physiotherapy is performed at the Mulia Hati General Hospital Kendari.